Contributions of cardiac "funny" (f) channels and sarcoplasmic reticulum Ca2+ in regulating beating rate of mouse and guinea pig sinoatrial node. Issue 12 (10th December 2015) - Nazarov, Islom B.; Schofield, Christopher J.; Terrar, Derek A.
Abstract: The aim of this study was to investigate the effects on spontaneous beating rate of mouse atrial preparations following selective block of cardiac "funny" (f) channels, I(f), and/or suppression of sarcoplasmic reticulum (SR) function in the absence and presence of β ‐adrenoceptor stimulation. ZD7288 [to block I(f)] caused a substantial reduction (222 ± 13 bpm) in beating rate from 431 ± 14 to 209 ± 14 bpm, ryanodine alone (to block SR Ca 2+ release) reduced beating rate by 105 ± 11 bpm, with subsequent addition of ZD7288 further reducing rate by 57 ± 9 bpm. Cyclopiazonic acid (CPA) alone (to inhibit Ca 2+ reuptake by the SR) reduced beating rate by 148 ± 13 bpm with subsequent addition of ZD7288 further reducing rate by 79 ± 12 bpm. In additional experiments measuring Ca 2+ transients in the SA node region using Rhod‐2, effects of ivabradine and ZD7288 on rate were again substantially reduced after CPA. Effects of CPA alone on rate developed much more slowly than effects on Ca 2+ transient amplitude. ZD7288, ivabradine, and CPA reduced the slope and maximum response of the log(concentration)–response curves for effects of isoprenaline on beating rate. Very little response to isoprenaline remained after treatment with CPA followed by ZD7288. Similar changes in isoprenaline log(concentration)–response curves were seen in guinea pig preparations. These observations are consistent with a role for Ca 2+ released from the SR in regulating I(f) and therefore beating rate of SA node preparations; there appear to be additional contributions of SR‐derived Ca 2+ to effects of β ‐adrenoceptor stimulation on beating rate that are independent of I(f). Abstract : The aim of this study was to investigate the effects on spontaneous beating rate of mouse atrial preparations following selective block of cardiac "funny" (f) channels, I(f), and/or suppression of sarcoplasmic reticulum (SR) function in the absence and presence of β ‐adrenoceptor stimulation. The observations are consistent with a role for Ca 2+ released from the SR in regulating I(f) and therefore beating rate of SA node preparations; there appear to be additional contributions of SR‐derived Ca 2+ to effects of β ‐adrenoceptor stimulation on beating rate that are independent of I(f).